Financing of small scale industries in a developing economy - Pareek, H. S. (New Delhi : National, 1978)
This book examines the financing of small scale industries in India in the 1970's with particular reference to: the socio-economic setting, role and problems of small scale industries, capital structure, state agency, commercial banks, co-operative agencies among others.
Includes index.
Includes bibliographical references: p. [267]-274.
lje 10/04/2018
Loans
Keywords: Small business--Finance; Small business; Small scale industries; SME- developing economy; India--Rajasthan; India